Benefício de Prestação Continuada: entre as políticas de Previdência Social e Assistência Social - Oliveira, Antonia Pereira de (2023)
The dissertation presents the analysis of the federal trajectory of the Continuous Provision Benefit (BPC) in the Social Assistance Policy and Social Security, in dialogue with municipal experiences in the State of São Paulo, based on the critical social theory that considers the historicity, and the movement continuum of reality and its contradictions. The BPC guaranteed in the 1988 Constitution and regulated by the Organic Law of Social Assistance (LOAS) in 1993, guarantees a monthly transfer in the amount of one minimum wage to people with disabilities and the elderly from 65 years old, who have a per capita income of up to one quarter of the minimum wage and cannot be provided for by their families. This study aims to analyze the management and operation of the BPC, demarcating aspects that restrict or expand access to the benefit during its historical trajectory, investigating its nature and conformation within the scope of Social Security. The methodology adopts a qualitative approach, combining bibliographical, documentary and field research, using interview techniques and focus groups with SUAS managers and workers, respectively. We found that throughout the history of the BPC the eligibility criteria were changed several times, which still a challenge for the Social Assistance Policy the conceptual alignment on family, income, family group and disability in the analysis for granting the BPC. The study showed a distance between the national coordination of the Social Assistance Policy and the operational management of the benefit in the INSS, allowing Social Security to incorporate social security features into the BPC, distancing itself from its identity as a social assistance right and creating barriers in accessing the benefit to the claimant population. The research indicates that it is necessary to improve the BPC management model, integrating the benefit operation with the management of the Social Assistance Policy, in a planned, gradual way and with financial incentives for the federated entities, so that the BPC can become effective as a right and socioassistance benefit within the SUAS